2018
DOI: 10.1002/macp.201800333
|View full text |Cite
|
Sign up to set email alerts
|

Exceptionally High CO2 Adsorption at 273 K by Microporous Carbons from Phenolic Aerogels: The Role of Heteroatoms in Comparison with Carbons from Polybenzoxazine and Other Organic Aerogels

Abstract: Phenolic aerogels containing oxygen and other polymeric aerogels containing both oxygen and nitrogen (polybenzoxazine and a polyamide‐polyimide‐polyurea co‐polymer) are converted to carbon aerogels (800 °C/Ar), and are etched with CO2 (1000 °C). Etching opens closed pores and increases micropore volumes and size. Heteroatoms are retained in the etched samples. All carbon aerogels are evaluated as CO2 absorbers in terms of their capacity and selectivity toward CH4, H2, and N2. CO2 adsorption capacity is linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 87 publications
2
46
1
Order By: Relevance
“…Within the past decade, polybenzoxazines have been found to be extremely effective in adsorbing CO 2 from air streams, which is crucial for reducing industrial pollution and weakening the effects of global warming from carbon emissions [37,[106][107][108][109][110][111]. Many studies attributed this ability to the porous qualities of benzoxazine, particularly the micropore volume and BET surface area.…”
Section: As Adsorbents Co 2 Capturementioning
confidence: 99%
“…Within the past decade, polybenzoxazines have been found to be extremely effective in adsorbing CO 2 from air streams, which is crucial for reducing industrial pollution and weakening the effects of global warming from carbon emissions [37,[106][107][108][109][110][111]. Many studies attributed this ability to the porous qualities of benzoxazine, particularly the micropore volume and BET surface area.…”
Section: As Adsorbents Co 2 Capturementioning
confidence: 99%
“…Organic aerogels can be made from Resorcinol/Formaldehyde (RF) [ 53 , 54 , 55 , 56 ], 2,4-dihydroxybenzoic acid (DHBA)/F [ 57 ], Phenol/Formaldehyde (P/F), Melamine/F (MF) [ 58 ], Polyurethane-Dichloromethane [ 59 ], Cresol/Formaldehyde (CF) [ 60 ], RF/CTAB [ 55 ], Pararosaniline base (PAB) and 1,3,5-triformylbenzene (TFB), Phloroglucinol-formaldehyde (FPOL) [ 61 ], Phloroglucinol-terephthalaldehyde (TPOL) [ 61 ], Poly(vinyl alcohol) PVA aerogels [ 62 ], Carbon nanotubes (CNT) [ 63 ], and Graphene [ 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Different catalysts are usually used to prepare RF aerogel [ 71 ].…”
Section: Organic Aerogelsmentioning
confidence: 99%
“…Table 2 synopsizes the various studies mentioned in this section, including their precursors, activation methods and, of course, CO 2 -adsorption capacity. Amongst all organic aerogels listed in Table 2, the etched CAs prepared by Majedi far et al show the highest CO 2 -sorption capacity up to 14.8 ± 3.9 mmol•g −1 due to their extremely high surface area created by etching [61]. However, between the organic aerogels, bio-based aerogels such as celluloses have recently attracted much attention with excellent properties, such as being environmentally friendly, renewable, biocompatible, biodegradable, as well as being inexpensive.…”
Section: Organic Aerogelsmentioning
confidence: 99%
“…Current research has focused on increasing the specific surface area (SSA) and controlling the pore size distribution (PSD), since the adsorption capacity is closely related to the textural characteristics of the carbon materials [22,23,24]. For example, Leventis et al [25,26] reported that microporous carbon aerogels demonstrated an exceptionally high adsorption capacity for CO 2 . Meanwhile, for the purpose of improving the adsorption efficiency and further enhancing the interactions between gas molecules and carbon material, it is important to incorporate heteroatoms (i.e., N, P, S) into the carbon framework [21,22,25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Leventis et al [25,26] reported that microporous carbon aerogels demonstrated an exceptionally high adsorption capacity for CO 2 . Meanwhile, for the purpose of improving the adsorption efficiency and further enhancing the interactions between gas molecules and carbon material, it is important to incorporate heteroatoms (i.e., N, P, S) into the carbon framework [21,22,25,26,27,28]. Recently, many efforts have been devoted to the synthesis of robust porous carbon that possesses high adsorption capacity and good selectivity, especially the N-doped porous carbon adsorbent.…”
Section: Introductionmentioning
confidence: 99%